کتب علوم الحدیث میں امثال فقہیہ پر اختلاف مسالک کے اثرات؛ ایک تحقیقی جائزہ: The effects of differences of Masalik on the Jurisprudential proverbs stated in the books of hadith studies - Ata-ul-Mustafa, Muhammad; Qāsim, Dr. Hafiz Masood (Al-Amīr Research Journal for Islamic Studies, 2023)
The foundation of the Sharia is revelation, revelation is the name of two things, the Qur’an and the Sunnah, since both are related to the news, and to convey the news to others, narrators are needed, so for the propagation of the Qur’an and the Sunnah to future generations. It was necessary to have narrators, the narrators of the Holy Qur’an are called Qira, the narrators of the Sunnah are called Muhaddith, the traditions of the Holy Qur’an are called ’Qara’at’ and the traditions of the Sunnah are called ’Ahadith’. Both the Qur’an and the Sunnah are revelations, but still there are some differences between them which are explained in detail in the Book of Principles. It was a difficult task, and the significant efforts made by the Muhadditheen in this regard were more famous and campaigned than the knowledge of al-Qaraat and recitation. He became famous with this, and some people even got the wrong impression that he had nothing to do with jurisprudence, and this wrong impression was reinforced by the behavior of the some Narrators. In reasoning and deriving from the Sunnah, there were many disorders and factors that gave birth to different schools of jurisprudence. For example, a hadith revealed to an imam or a jurist during reasoning has a hidden reason that is not revealed to anyone else. Therefore, there is a difference in argumentation. Similarly, sometimes the hadeeth is correct in a certain issue in front of a jurist, while on the other hand, it is weak in the opinion of another, which leads to diversity in argumentation. When the jurists differed in the derivation of the issues and rulings, in fact, these are cases of priority and non-priority, in which there is, however, scope that any position can be declared preferred based on arguments. Keywords: Hadith, Muhaddithin, Jurisprudential Proverbs, School of Thoughts, Differences.